2020
DOI: 10.1177/1758835920968725
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of abiraterone acetate plus prednisone in chemotherapy-naïve patients with metastatic castration-resistant prostate cancer in a large prospective real-world cohort: the ABItude study

Abstract: Background: Real-world data on chemotherapy-naïve patients with metastatic castration-resistant prostate cancer (mCRPC) treated with abiraterone plus prednisone are limited, largely deriving from small retrospective studies. Methods: ABitude is an Italian, observational, prospective, multicenter study of mCRPC patients receiving abiraterone plus prednisone in clinical practice. Chemotherapy-naïve mCRPC patients were consecutively enrolled at abiraterone start (February 2016 to June 2017) and are being followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Using an unselected cohort of patients from several oncology, urology, and radiotherapy sites across Italy, the final analysis of the ABItude study over a 36-month study period showed the real-world effectiveness and safety of abiraterone for the treatment mCRPC patients naive to chemotherapy, confirming results from the interim analysis. 16 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using an unselected cohort of patients from several oncology, urology, and radiotherapy sites across Italy, the final analysis of the ABItude study over a 36-month study period showed the real-world effectiveness and safety of abiraterone for the treatment mCRPC patients naive to chemotherapy, confirming results from the interim analysis. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Collecting prospectively hard oncologic endpoints and relevant patient-reported outcomes (PROs) on a large cohort of unselected patients, it represents a unique opportunity to evaluate the effectiveness and safety of abiraterone in the treatment of chemotherapy-naive mCRPC patients in routine clinical practice. Results from interim analyses at 18 months 16 of median follow-up showed favorable patient outcomes and no safety-related concerns. Herein, we have reported the final 36-month results of the ABItude study.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…18 In particular, the present results are in agreement with those from a large prospective Italian cohort of first-line mCRPC patients followed 3 years, in which abiraterone acetate plus prednisone showed good clinical (and patients' reported) outcomes. 19 Our results on docetaxel are broadly comparable to those observed in a trial comparing the drug given as firstline treatment for mCRPC against cabazitaxel, which estimated a median OS of 24.3 months and a median PFS of 5.3 months in the docetaxel arm; 20 any comparison with the two 2004 landmark trials 5,7 is likely to be misleading, because of the limited available treatment options for mCRPC and the different patients' characteristics and disease management at the time of trials conduction.…”
Section: Discussionmentioning
confidence: 99%
“… 18 In particular, the present results are in agreement with those from a large prospective Italian cohort of first-line mCRPC patients followed 3 years, in which abiraterone acetate plus prednisone showed good clinical (and patients’ reported) outcomes. 19 …”
Section: Discussionmentioning
confidence: 99%